Post-transcriptional regulation activity through alternative splicing involved in the effects of Aloe vera on the Wnt/β-catenin and Notch pathways in colorectal cancer cells - Chang Peng; WeiJia Zhang; Xue Shen; YueMei Yuan; Yan Li; Wei Zhang; MeiCun Yao (Elsevier, 2020)
Aloe vera (L.) Burm.f. is widely used as laxative drugs, cosmetics, and functional food due to a variety of therapeutic effects. However, several studies indicated a colonic carcinogenic activity of Aloe vera. But the underline mechanism has not been well clarified. This study aimed to explore the potential mechanism at the post-transcriptional level. Identification of Differential Expressed Alternative Splicing (DEAS) genes and events and the corresponding functional enrichment analyses were conducted on RKO cells after treated with Aloe vera aqueous extract and its two active components, aloin and aloesin. And RT-qPCR was conducted for validation. Results indicated that they induced 2200, 2342 and 2133 DEAS events, respectively. The GO enrichment and the COG classification results of DEAS genes showed that they were associated with transcription, as well as functions like signal transduction mechanisms. Moreover, DEAS genes related to the two colorectal cancerous pathways, Wnt and Notch pathways, were annotated. In conclusion, aloe extract, aloin and aloesin significantly regulated the DEAS profile of RKO cells. The colonic carcinogenicity of Aloe vera may due to its post-transcriptional regulatory activity through Alternative Splicing (AS) on genes, especially on Wnt-related and Notch-related key genes.